The prognostic impact of immune-related adverse events during anti-PD1 treatment in melanoma and non–small-cell lung cancer: a real-life retrospective study. (1st January 2020) - Dupont, R.; Bérard, E.; Puisset, F.; Comont, T.; Delord, J.-P.; Guimbaud, R.; Meyer, N.; Mazieres, J.; Alric, L.
ABSTRACT: Background : Nivolumab and pembrolizumab, two PD1 inhibitors, trigger immune-related adverse events in approximately 50% of patients. Our objective was to determine whether these immune-related adverse events are associated with patient outcomes. Patients and Methods : Retrospective cohort study, realized at the Institut Universitaire du Cancer de Toulouse, of all the patients treated with nivolumab or pembrolizumab off clinical trials. We included patients (i) diagnosed with unresectable stage III or stage IV melanoma or with recurrent stage IIIB or stage IV non-small cell lung cancer (ii) on nivolumab 3mg/kg or pembrolizumab 2mg/kg every 2 or 3 weeks respectively. Results : Of the 311 patients included (of 641 eligible subjects), 120 (38.6%) had melanoma and 191 (61.4%) had non-small cell lung cancer; 241 (77.5%) were treated with nivolumab with a median follow-up of 24 months (20–29). We observed 166 immune-related adverse events in 116 (37.3%) patients, categorized as "early" (onset before 12 weeks in melanoma and before 8 weeks in lung cancer) in 63 (54.3%) patients. Early and late adverse events were significantly associated with an increase in overall survival: adjusted hazard ratio 0.58 [0.41–0.84] ( p = .003) and 0.28 [0.16–0.50] ( p < .001) respectively. The overall response rate was significantly increased in patients with an immune-related adverse event (53.9% vs 12.9%, p < .001) Conclusions : This study validates the association between immune-related adverse events and anti-PD1 efficacy in real-life, especially if these events are delayed. Our results, along with further studies on the place of immunosuppressive drugs in the therapeutic strategy, could improve the management of these adverse events.